2017
DOI: 10.3892/etm.2017.5304
|View full text |Cite
|
Sign up to set email alerts
|

Apelin as a novel drug for treating preeclampsia

Abstract: Preeclampsia is a pregnancy-specific disorder of new-onset hypertension and proteinuria after 20 weeks' gestation, often resulting in poor outcome. Previous studies demonstrated that apelin is an endogenous active peptide with visodilation and anti-oxidative stress capabilities. The present study investigated the effects of apelin in a rat model of preeclampsia induced by reduced uterine perfusion pressure (RUPP). Rats with RUPP displayed hypertension and poor pregnancy outcomes, such as decreased fetal and pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 38 publications
(36 reference statements)
3
54
0
Order By: Relevance
“…Because hypoxia stimulates apelin expression and the placenta is the major site for apelin synthesis and secretion (14,35), exercise-induced placental hypoxia might explain the elevated fetal apelin concentration. As a peptide, maternal apelin is not expected to cross the placental barrier (36). In agreement, we found that apelin was elevated following exercise in both maternal and fetal circulation and BAT, suggesting that the apelinergic system may be a therapeutic target promoting fetal brown adipogenesis, thus maintaining metabolic homeostasis.…”
Section: Downloaded Fromsupporting
confidence: 79%
“…Because hypoxia stimulates apelin expression and the placenta is the major site for apelin synthesis and secretion (14,35), exercise-induced placental hypoxia might explain the elevated fetal apelin concentration. As a peptide, maternal apelin is not expected to cross the placental barrier (36). In agreement, we found that apelin was elevated following exercise in both maternal and fetal circulation and BAT, suggesting that the apelinergic system may be a therapeutic target promoting fetal brown adipogenesis, thus maintaining metabolic homeostasis.…”
Section: Downloaded Fromsupporting
confidence: 79%
“…Notably, Yamaleyeva et al found 30% lower content of apelin in the chorionic villi of preeclamptic patients compared to villi obtained from women with a normal gestation and proposed that lower apelin levels in the preeclamptic placenta might diminish its opposing modulation of vasoconstrictor mediators, which results in the increased blood pressure defining PE [259]. Indeed, the blood pressure-lowering action of apelin is well documented in several animal models and in patients with heart failure [263] and apelin is known to act on vascular smooth muscle cells, inducing either vasodilatation or vasoconstriction via different pathways [259]. Additionally, in the study of Yamaleyeva et al, apelin release from the chorionic villi was reduced by angiotensin II administration, suggesting a potential interaction between apelin and the renin-angiotensin system [259].…”
Section: Adipokines and Female Reproductive Pathologiesmentioning
confidence: 99%
“…The beneficial effects of apelin in PE have also been suggested by a very recent report using a rat model in which PE symptoms were induced by reducing uterine perfusion pressure. In this model, apelin treatment significantly reversed the elevation in blood pressure and increased the total foetal weight, resulting in higher embryo survival rates [263]. Interestingly, these effects were obtained by improving the impaired eNOS/NO (endothelial nitric oxide synthase/nitric oxide) signalling pathway and preventing the activation of oxidative stress, which is one of the key features of PE pathogenesis [263].…”
Section: Adipokines and Female Reproductive Pathologiesmentioning
confidence: 99%
“…Increased systemic oxidative stress is a central hypothesis to the development of vascular dysfunction in preeclampsia, which primarily affects endothelial function. Many studies using the RUPP model have shown increased vascular 37,63,64 , maternal blood 48,53,63,65 , renal 66 , placental 48,49,52,53,6668 , and amniotic fluid 69 oxidative stress. Concurrently, the renal 55,68 , maternal blood 47,53 , placental 49,55 , and amniotic fluid 55 antioxidant capacity has been shown to be reduced.…”
Section: Discussionmentioning
confidence: 99%